Lonicera flos and Curcuma longa L. extracts improve growth performance, antioxidant capacity and immune response in broiler chickens - Xu, Dahai; Wang, Xiao; Shi, Wanyu; Bao, Yongzhan (Frontiers in Veterinary Science, 2024)
Alternatives to antibiotics are urgently needed to maintain broiler growth and health. The present study was conducted to evaluate the effects of Lonicera flos and Curcuma longa L. extracts (LCE) as antibiotic substitutes on growth performance, antioxidant capacity and immune response in broilers. A total of 480 one-day-old female broilers (WOD168) were allocated to 3 treatments with 5 replicates of 32 birds for 35 days. The 3 treatments were: an antibiotic-free basal diet (control, CON), CON + 50 mg/kg spectinomycin hydrochloride and 25 mg/kg lincomycin hydrochloride (ANT), CON + 500 mg/kg LCE (LCE). During the entire experimental period, supplementation of ANT and LCE increased (P < 0.01) average daily gain (ADG) and decreased (P < 0.05) feed conversion ratio (FCR), thereby resulting in greater final body weight (BW) compared with CON. Dietary LCE supplementation increased (P < 0.05) serum (glutathione peroxidase) GSH-Px, (superoxide dismutase) SOD and total antioxidant capacity (T-AOC) activities, and decreased (P < 0.05) serum malonaldehyde (MDA) concentration at d 35 compared with CON. There was no significant difference in serum catalase (CAT) activity among treatments. Birds in LCE group had lower (P < 0.05) MDA concentration and higher SOD activity in liver than those in CON and ANT groups at d 35.Birds in LCE group had higher (P < 0.05) phagocytic index and serum antibody titers to Newcastle disease virus (NDV) than those in CON group. Lower (P < 0.05) concentrations of pro-inflammatory cytokines and higher (P < 0.05) concentrations of anti-inflammatory cytokines in serum and liver were observed in birds fed LCE diet than those fed CON diet. In conclusion, dietary supplementation of LCE improved growth performance by enhancing antioxidant capacity, strengthening immune system and alleviating inflammation, which has potential as antibiotic alternatives.